The association between temporomandibular disorders and kinematics of the sacroiliac joint: a 3D motion analysis study - Leila Rahnama; Ahmad Bahramian Parchekouhi; Noureddin Karimi; Ali barzegar (BMC Musculoskeletal Disorders)
Abstract Background Temporomandibular disorders (TMDs) have been the focus of many studies, but the relationship between TMDs and other body segments, such as the pelvis, remains controversial. This study aimed to investigate the relationship between TMD and kinematics of the sacroiliac joint. Method Twenty participants with chronic TMD and 20 healthy individuals were included in this study. The temporomandibular joint range of motion, pain intensity, and TMD severity were documented. The three-dimensional kinematics of the sacroiliac joint were recorded during a trunk flexion task using a motion analysis system and MATLAB software. Results The severity of TMD had a significant association with pain intensity in the patient group. At the starting position (before forward flexion of the trunk), we found significant differences in the linear and angular positions of the sacrum relative to the ilium in the sagittal plane and around the frontal axis on both sides between groups. Conclusion Our results indicated significant differences in some parameters between the healthy and TMD groups, emphasizing altered sacroiliac joint kinematics associated with TMD. This study contributes to the ongoing discussion about the relationship between TMD and other areas of the body and highlights the importance of further research in this area. Trial registration Clinical Trial number is not applicable.